Investigation of Fe isotope systematics for the complete sequence of natural and metallurgical processes of Ni lateritic ores: Implications for environmental source tracing. (April 2021) - Ratié, Gildas; Garnier, Jérémie; Vieira, Lucieth Cruz; Araújo, Daniel F.; Komárek, Michael; Poitrasson, Franck; Quantin, Cécile
Abstract: Metal isotopes are versatile pollutant source trackers, but biogeochemical processes can overprint or alter the original source isotopic fingerprint and thus hinder contamination tracing. Here, we explore Fe isotope systematics for the complete range of natural and metallurgical processes related to Ni lateritic ores from Barro Alto, Brazil, to assess its potential as a tracer in polluted lateritic soil contexts developed in an ultramafic system. The homogeneous δ 57 Fe values from protolith to soil confirmed that no significant Fe isotopic variation occurred during the formation of the deep lateritic profile. In addition, no Fe isotopic fractionation was found during the smelting process. Although the δ 57 Fe values resulting from mining activities fall within the range of terrestrial sample signatures, the conservation of the δ 57 Fe values from the ores to the by-products is an advantage for tracing anthropogenic sources when (i) the pyrometallurgical plant uses feeding material with Fe ores imported from other geological formations exhibiting different δ 57 Fe values and/or (ii) the by-products are transported or dispersed to other locations with different δ 57 Fe signatures in the topsoil. Graphical abstract: Image 1 Highlights: Fe mobility does not induce isotopic fractionation during chemical weathering. There is no evidence of Fe isotope fractionation during the RKEF smelting process. Smelting slags are stamped with δ 57 Fe values from Ni laterite ores. The use of Fe isotopes as an environmental tracer in lateritic soils is limited. Fe isotopes may be a potential tracer of mining activities in non-lateritic soils.